2022
DOI: 10.3389/fonc.2022.841460
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dynamic-Enhanced MRI and Intravoxel Incoherent Motion Diffusion−Weighted Imaging for Prediction of the Pathological Response to Neoadjuvant Chemotherapy and the Prognosis in Locally Advanced Gastric Cancer

Abstract: BackgroundThis study aimed to explore the predictive value of quantitative dynamic contrast-enhanced MRI (DCE-MRI) and intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) quantitative parameters for the response to neoadjuvant chemotherapy (NCT) in locally advanced gastric cancer (LAGC) patients, and the relationship between the prediction results and patients’ prognosis, so as to provide a basis for clinical individualized precision treatment.MethodsOne hundred twenty-nine newly diagnosed LAGC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In this study, similar to ADC values, lower Dslow values before treatment also indicated more sensitive treatment response of immunochemotherapy, and the diagnostic performance of the Dslow value was superior to the ADC value, which was consistent with previous research results [ 31 33 ]. This result can be explained by the imaging principles of IVIM, which can effectively separate the diffusion of pure water molecules and the microcirculation components of tissues using the bi-exponential model, therefore, IVIM-derived Dslow value can more truly reflect the diffusion of water molecules.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, similar to ADC values, lower Dslow values before treatment also indicated more sensitive treatment response of immunochemotherapy, and the diagnostic performance of the Dslow value was superior to the ADC value, which was consistent with previous research results [ 31 33 ]. This result can be explained by the imaging principles of IVIM, which can effectively separate the diffusion of pure water molecules and the microcirculation components of tissues using the bi-exponential model, therefore, IVIM-derived Dslow value can more truly reflect the diffusion of water molecules.…”
Section: Discussionsupporting
confidence: 92%
“…This exacerbates the degree of barrier destruction and so the proportion of extracellular space outside the blood vessels and, consequently, V e increase. This is believed to be the reason for the link between poor prognosis and high V e values[ 22 , 23 ]. In a study on dynamic contrast enhanced-MRI quantitative parameters for predicting the efficacy of concurrent chemoradiotherapy for locally advanced cancer, Liu et al [ 24 ] discovered tumor regression when V e was low, which could be used as a potential indicator to predict the treatment response of locally advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CT scans, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has been used to develop prediction models. Zhu et al [ 50 ] reported an AUC of 0.922 by combining parameters from DCE-MRI and intravoxel incoherent motion diffusion-weighted imaging to predict 2-year DFS in patients receiving NAC.…”
Section: Predictors Of Nac Outcomes In Gastric Cancermentioning
confidence: 99%